Gadjah Mada University: promoting health where and when it matters - Seetha Govindaraju; Rozelle Ashwini Walters (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
The epidemiological transition of disease in Indonesia puts non-communicable diseases (NCDs) responsible for an estimated 71% of total deaths. Reflecting that horrifying statistic, 143 Gadjah Mada University students from the Faculty of Engineering were screened by medical students from the Faculty of Medicine, Nursing and Public Health to find 37,6% overweight and 59,4% having high blood pressure. Is it safe to conclude that the best educated youth in Indonesia are unaware that their present lifestyle choices will cause potentially morbid consequences to their health in the future? This revelation came from a collaboration between the two faculties to promote health among a population where it is very possible to make significant changes. As part of their clinical rotations, medical students had trained staff from the engineering faculty to pioneer a monthly health screening program for students. The training involved a demonstration of the set up which consisted of five posts; registration, assessment of risk factors, measurement of body mass index (BMI), physical examination and counselling. This program taught us that multiple training sessions are required to equip non-medical staff with necessary information to counsel students on practical steps needed in mitigating lifestyle changes. Standardized information and commitment among trainers is essential to enable a uniform understanding among trainees. However, despite the staggering health status of students, this allows for innovative solutions. Perhaps an inter-faculty buddy system can be implemented which bases science instead of trendy fads to maintain and promote health. If a healthy status is a prerequisite for admission to tertiary institutions, then could it be mandated upon graduation too? We can respond to this epidemiological transition with one of our own; empowering people to change their health behaviors before it changes them.